Pengaruh Iklan Mie Sedaap Semua Varian (Korean Spicy Chicken) Di Televisi Nasional Terhadap Minat Beli Warga Kabupaten Jember - Jessy A, Febby Mauliana; Putra, Ferdian Ardani (Program Studi Ilmu Komunikasi, 2024)
Advertising was an important way for brands and consumers to communicate and promote products. Television advertising was considered the most effective method to reach a wide audience. Through advertisements, companies hoped to cultivate buying interest in the minds of the public. One instant noodle producer that used this marketing strategy was Mie Sedaap. This study aimed to determine the influence of Mie Sedaap All Variants (Korean Spicy Chicken) advertisements on national television on the buying interest of the residents of Jember Regency. The research method used was a quantitative approach with a survey type of research. This study referred to the Sociopsychological theory and the Influence tradition. The research subjects were selected using non-probability sampling with purposive sampling technique. The data collection technique was carried out using questionnaires, involving 59 respondents. The research results showed that the t-value was 1.375, which was smaller than the t-table of 2.002, leading to the conclusion that Ho was accepted and Ha was rejected. Additionally, the significance value of 0.175 indicated that there was no influence of Mie Sedaap advertisements (X) on buying interest (Y). Therefore, it could be concluded that Mie Sedaap All Variants (Korean Spicy Chicken) advertisements on national television did not influence the buying interest of the residents of Jember Regency.